INFORAT: Renewable Natural Resources Information and Documentation Center for Tropical America - CATIE - Centro Agronómico Tropical de Investigación y Enseñanza (CATIE, Turrialba (Costa Rica). Dept. de Recursos Naturales Renovables, 2014)
20 pág, 1 tab.